Progress of research of prevention and integrated traditional Chinese and western medicine nursing of peripherally inserted central catheter-related complications (经外周中心静脉置管相关并发症的预防及中西医护理进展) - WANG Shuang (王爽); PENG Wei (彭伟); WANG Jing (王净); QIAO Shouang (乔首昂); YANG Jianpan (杨健盼); JIA JIngyu (贾静宇); HOU Kai (侯凯); LI Jinghuan (李靖嬛) (Journal of International Translational Medicine Limited, 2023)
The peripherally inserted central catheter has been widely used in clinical setting because of its advantages of easy-to-use, safe and long‐term indwelling. Doctors and nurses should pay more attention on PICC-related complications during treatment. This paper summarized the common PICC-related complications and it influencing factors and nursing countermeasures, and provided reference for quality improvement of PICC maintenance. (经外周中心静脉置管(PICC)具有操作简单、安全可靠、留置时间长等优势, 在临床应用广泛。PICC相关并发症的防治是医护人员关注的重点。本研究总结了常见的PICC相关并发症, 并对相关影响因素和护理对策进行了归纳, 旨在为进一步提高PICC使用质量提供参考。)